2006
DOI: 10.1161/01.res.0000202804.84885.d0
|View full text |Cite
|
Sign up to set email alerts
|

GDF15/MIC-1 Functions As a Protective and Antihypertrophic Factor Released From the Myocardium in Association With SMAD Protein Activation

Abstract: Abstract-Here we identified growth-differentiation factor 15 (GDF15) (also known as MIC-1), a secreted member of the transforming growth factor (TGF)-␤ superfamily, as a novel antihypertrophic regulatory factor in the heart. GDF15 is not expressed in the normal adult heart but is induced in response to conditions that promote hypertrophy and dilated cardiomyopathy. To elucidate the function of GDF15 in the heart, we generated transgenic mice with cardiac-specific overexpression. GDF15 transgenic mice were norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
380
2
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(418 citation statements)
references
References 42 publications
22
380
2
14
Order By: Relevance
“…MIC-1 has not been widely studied in inflammation; however, we found that serum levels of MIC-1 independently predicted atherosclerotic events (20), and MIC-1 itself is associated with tissue remodeling in cardiac damage (30). Like RA, atherosclerosis is a macrophage-mediated chronic inflammatory disease.…”
mentioning
confidence: 73%
“…MIC-1 has not been widely studied in inflammation; however, we found that serum levels of MIC-1 independently predicted atherosclerotic events (20), and MIC-1 itself is associated with tissue remodeling in cardiac damage (30). Like RA, atherosclerosis is a macrophage-mediated chronic inflammatory disease.…”
mentioning
confidence: 73%
“…Experimental studies have shown that GDF-15 expression significantly increases in the heart after various forms of stress, including pressure overload 22,23 . Animal studies have shown that GDF-15 promotes protective, antiapoptotic and antihypertrophic effects in the heart 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that GDF-15 promotes protective, antiapoptotic and antihypertrophic effects in the heart 23 . Considering the fact that GDF-15 is produced by several other cell types in addition to cardiomyocytes (endothelial cells, adipocytes, macrophages, vascular smooth muscle cells), it is likely that this biomarker integrates information from different disease pathways, providing a pathophysiological insight in patients with HFnEF.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective study analyses have shown that high levels of GDF-15 are associated with increased risk of death and/or repeated AMI [14]. According to some data, this biomarker is a more accurate marker of CHF with preserved left ventricular (LV) ejection fraction while natriuretic peptide (NUP) better shows the course of systolic heart failure [15].The level of GDF-15 correlates with the severity of CHF manifestations and LV diastolic dysfunction indices [8].…”
Section: Problem Statement and Analysis Of The Recent Researchmentioning
confidence: 99%